2017
DOI: 10.1107/s241431461701207x
|View full text |Cite
|
Sign up to set email alerts
|

1-Vinyl-4-imidazoline-2-thione

Abstract: The title compound, C5H6N2S, was obtained by deprotonation of 1-vinylimidazole and subsequent reaction with elemental sulfur. In the crystal, the molecules are linked by N—H...S and C—H...S hydrogen bonds, and arranged in layers parallel to theabplane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Anyway, the final removal of the imidazole C2-proton is still lacking mechanistic clarification. For example, own experiments 16 showed that deprotonation of 1-vinylimidazole using strong bases, such as isopropylmagnesium chloride proceeds satisfactorily (with subsequent addition of elemental sulfur yielding 1-vinyl-4-imidazoline-2-thione, hereby confirming the desired attack at the C2-position). Upon addition of isolated arenediazonium tetrafluoroborates to 1-vinylimidazole solutions in THF, the reaction mixture immediately undergoes a red coloration, but, disappointingly, no N-vinylated phenylazoimidazole system could be straightforwardly isolated so far.…”
Section: Synthetic Considerationsmentioning
confidence: 93%
“…Anyway, the final removal of the imidazole C2-proton is still lacking mechanistic clarification. For example, own experiments 16 showed that deprotonation of 1-vinylimidazole using strong bases, such as isopropylmagnesium chloride proceeds satisfactorily (with subsequent addition of elemental sulfur yielding 1-vinyl-4-imidazoline-2-thione, hereby confirming the desired attack at the C2-position). Upon addition of isolated arenediazonium tetrafluoroborates to 1-vinylimidazole solutions in THF, the reaction mixture immediately undergoes a red coloration, but, disappointingly, no N-vinylated phenylazoimidazole system could be straightforwardly isolated so far.…”
Section: Synthetic Considerationsmentioning
confidence: 93%